1994
DOI: 10.1111/j.1365-2761.1994.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio anguillarum serovars associated with vibriosis in fish

Abstract: A total ol" 317 Vibrio anguillantm strains isolated from diseased fish together with 14 V. anguillarum serogroup O2 and V. ordalii type strains were serotyped using the European scrotyping system. Marked speeies difterenees were reeorded. In isolates from belonged to other serogroups or were non-typeablc. Figures for turbot were similar to those from salmonids. In 32 isolates from sea bass, sea bream and mullet, most strains belonged to serogroup Ol. while one was O2a. one O7, and the rest non-typcable In cod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 27 publications
3
96
1
2
Order By: Relevance
“…Strains were isolated in our laboratory or received from various other laboratories. 0-serotyping 0-serotyping was carried out using the slide agglutination method as previously described [23,24]. The strains were tested for reactivity with the 10 antisera, 01-010, described in the European serotyping system [24], and with seven additional antisera, temporarily designated [26] and subjected to electrophoresis in 0 8 % agarose gels (SeaKem GTG, FMC BioProducts, Rockland, ME, USA) in TAE (Tris 40 mm, sodium acetate 5 mM, ethylenediaminetetraacetate (EDTA) 1 mM; pH 8 0).…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Strains were isolated in our laboratory or received from various other laboratories. 0-serotyping 0-serotyping was carried out using the slide agglutination method as previously described [23,24]. The strains were tested for reactivity with the 10 antisera, 01-010, described in the European serotyping system [24], and with seven additional antisera, temporarily designated [26] and subjected to electrophoresis in 0 8 % agarose gels (SeaKem GTG, FMC BioProducts, Rockland, ME, USA) in TAE (Tris 40 mm, sodium acetate 5 mM, ethylenediaminetetraacetate (EDTA) 1 mM; pH 8 0).…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…All strains were stored at -80°C until used and propagated on blood agar plates (Marine agar (Difco) supplemented with 5 % sterile, citratestabilized calf blood), incubated at 20°C for 2 days. 0-serotyping 0-serotyping was carried out using the slide agglutination method as previously described [9,19]. Absorbed 02a and 02b sera were obtained as described by Larsen and colleagues [9].…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…0-serotyping 0-serotyping was carried out using the slide agglutination method as previously described [9,19]. Absorbed 02a and 02b sera were obtained as described by Larsen and colleagues [9].…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies describe V. ordalii isolated from salmon as a biochemically, serologically and geneti-cally homogeneous taxon (Mutharia et al 1993, Larsen et al 1994, Grisez & Ollevier 1995, Tiainen et al 1995, Toranzo et al 1997, although Silva-Rubio et al (2008) suggested the possibility that the Chilean strains constitute a new serological subgroup of this bacterial species. In addition to the fact that its taxonomic classification is still evolving, our understanding of the pathogenic mechanisms of V. ordalii is likewise incomplete.…”
Section: Introductionmentioning
confidence: 99%